Fragility Functions for Displacement-based Seismic Design of Reinforced Masonry Wall Structures. Issue 1 (2nd January 2022) - Lotfy, I.; Mohammadalizadeh, T.; Ahmadi, F.; Soroushian, S.
ABSTRACT: It is well understood that in the displacement-based seismic assessment of masonry shear wall structures, it is desirable to have an estimation for lateral deformation capacity of wall segments that are linked to their different damage levels. This study focuses on the development of experimental-based fragility functions for reinforced masonry shear walls subjected to in-plane seismic loading, which can be used in the next-generation displacement-based seismic design approaches. Hysteresis responses of 91 wall specimens and their damage progression patterns obtained from a series of experiments performed at The University of Texas at Austin and Washington State University are used to generate fragility functions for different demand levels. Various damage states are proposed within this study that are associated with commonly employed methods of repair, and these damage states represent different levels of flexure, diagonal shear, and sliding shear damage in reinforced masonry shear walls. Corresponding damage limit states are defined in terms of ratio of lateral deformations to the aspect ratio of wall segment as the demand parameter for flexural damage, while those limit states for diagonal and sliding shear damage is the normalized shear demand. This paper develops drift-based fragility functions for key damage states associated with the structural performance and reparability of reinforced masonry walls. This research also shows that the proposed demand parameters formulate a more accurate correlation between the demand parameters and the damage observed in the tests in masonry walls than does from story-drift ratio, which was previously the industry standard practice.